ПОРІВНЯЛЬНА ОЦІНКА СТІЙКОСТІ ГІДРОБІОНТІВ ДО УМОВ ЗОВНІШНЬОЇ ГІПОКСІЇ ТА АНОКСІЇ - Андреєнко, Т. I. (Marine Ecological Journal, 2023)
The information about the comparative resistance of hydrobionts to oxygen deficiency, physiological and metabolic aspects of adaptation of marine organisms to hypoxia and anoxia is presented. Comparing with other groups of organisms, relatively low sensitivity and high resistance to hypoxia was observed in mollusks and priapulids. In anoxic medium mollusks are the most resistant to anoxia among the invertebrate animals as well. Polychaete demonstrate lower resistance and the lowest resistance is revealed in crustaceans. It is shown that the survival of aquatic organisms during limited time in anoxic conditions depends on their tolerance to temperature of the environment, size and activity. It is noted that among the invertebrate animals the most resistant to anoxia are mollusks as well. Polychaete demonstrate lower resistance and the lowest resistance is revealed in crustaceans. Strategies of metabolism of sea inhabitants under hypoxia and anoxia conditions are examined. It is shown that resistant to anoxia mollusks have considerable resources of glycogen and aspartate in tissues and able to maintain aerobic metabolism orientation at extremely low concentration of oxygen in water.